The Perpetuity of Matriarchal Condition in Barbie Land of Greta Gerwig’s Barbie - Hariyono, Hariyono; Rengganis, Dewi Ayu; Pasopati, Rommel Utungga; Wijaya, Kusuma; Kartiningsih, Rindrah (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This journal explores the enduring matriarchal condition alongside the dominance of female figures in Barbie Land in Barbie movie. The study investigates the representation of gender roles and the implications of such structure in contemporary feminist discourse in Barbie Land. Through qualitative method and explorative approach, by examining the perpetuity of matriarchal condition, the journal aims to shed light on the broader narrative of female empowerment and its complexities in Barbie Land and Real-World contexts. This journal provides in-depth exploration of the perpetuation of matriarchal condition in Barbie Land, using Heide Gottner-Abendroth's theory of matriarchy as a framework to analyze its cultural and social significances. The analysis includes how matriarchal condition in Barbie Land shapes women as central beings that own properties, do various jobs, and indicates great leadership. In conclusion, through Barbie Land, matriarchal condition is based on cooperation, mutual support, and belief that women can be powerful leaders in their own rights. The movie challenges audience to rethink traditional power structures and to consider the benefits of a society where women are central to leadership and decision-making. It is also noted that movie of Barbie may provide intertwinements of literature and real-world experience regarding gender equality initiatives.